Cultural Texts, a Key to Communicative Competence in Third and Fourth Forms Secondary School in Goma - Babona, Ukobizaba Nduwayezu (Journal of Education and Practice, 2024)
Purpose: The work at hand examines the effects of cultural texts, integrated in the language teaching and learning, on students' communicative competence in third and fourth forms secondary school. It has been noticed that some teachers of English do not yet distinguish a literary (cultural) text from a scientific or technical one precisely while determining pedagogic purposes. Methodology: To gather data in this research, an experimental study was conducted in third and fourth forms secondary school in Goma. Findings: The overall findings have revealed that cultural texts influence both reading comprehension, retelling and interpretation skills, a real gateway to communicative competence enhancement. In other words, this study brings a new vision to the practice of communicative activities as currently carried out in Goma secondary schools. Unique contribution to theory, policy and practice: It arises English teachers' concern not only for the message expressed by the text, but also for the exploitation of students' cultural values and schemata to heighten their communicative competence.